The Role of Digital Health Literacy in Preventing Medical Misinformation on Social Media: Implications for Public Health Behavior - Yessy Dessy Arna (PT. Anagata Sembagi Education, 2026)
The rapid proliferation of medical misinformation on social media poses significant challenges to public health, influencing risk perception, vaccination decisions, and preventive behaviors. Digital health literacy has emerged as a potential protective factor that enables individuals to critically evaluate and apply online health information. This study aims to analyze the role of digital health literacy in preventing medical misinformation on social media and to examine its implications for public health behavior. A quantitative cross-sectional survey was conducted among 420 active social media users aged 18 years and above. Data were collected using a structured online questionnaire measuring digital health literacy, belief in medical misinformation, and health behavior indicators, including vaccination intention and information verification practices. Multiple regression and mediation analyses were performed to assess predictive relationships. The results indicate that higher digital health literacy significantly reduces belief in medical misinformation and positively predicts vaccination intention and proactive information verification. Belief in misinformation negatively affects vaccination intention, supporting its mediating role. Although causal inference remains limited, the findings suggest that strengthening digital health literacy can contribute to safer health behaviors. Integrating digital health literacy education with public health communication strategies is essential to counter misinformation in the social media era.